Systemic immune inflammation index as a predictor of disease severity in tetanus patients: A retrospective observational study. - Dai Cheng; Ding Wenying; Huang Jizheng; Sun Wei; Li Liang; Han Guolei; Yang Hao (PLoS ONE)
Objective This study aimed to analyze the predictive value of the systemic immune inflammation index (SII) for the severity of disease in tetanus patients. Methods Clinical data of 34 tetanus patients admitted to the Second People's Hospital of Fuyang from January 1, 2019 to December 31, 2022 were analyzed. Based on whether patients received intensive care unit (ICU) treatment after admission, the patients were divided into ICU and non-ICU groups. The diagnostic value of SII for the severity of tetanus was assessed. Results Among the 34 patients, 18 (52.90%) were classified into the ICU group, and 16 (47.10%) into the non-ICU group. There were statistically significant differences in white blood cell count, platelet count, neutrophil count, and SII between the two groups (P<0.05). Logistic regression analysis revealed that SII was a risk factor for tetanus patients requiring ICU treatment. The area under the curve (AUC) for SII predicting ICU treatment in tetanus patients was 0.896 (95% CI 0.790-1.000, P<0.001). Conclusion The SII can serve as an objective predictive indicator for tetanus patients requiring ICU treatment.